DAMPAK STRES AKADEMIK TERHADAP KEMAMPUAN PENYELESAIAN KONFLIK SISWA DI SEKOLAH (STUDI LITERATUR) - Yadi Suryadi; Danny Meirawan (Business Finance Analyst Co., 2024)
This literature study discusses the impact of academic stress on students' conflict resolution abilities at school. Academic stress, arising from pressure for high achievement, competition, and high expectations, has become the focus of increasing attention among educators, parents, and researchers. Recent studies show that academic stress can impact students' overall well-being, including their ability to manage and resolve conflict in the school environment. The results of literature studies show that students who experience academic stress tend to experience decreased communication, empathy, and emotional management skills, which are key components of effective conflict resolution abilities. Apart from that, academic stress can also affect students' ability to think critically and creatively in resolving conflicts. This can hinder the conflict resolution process, worsen relationships between students, and affect overall student learning outcomes. Thus, the conclusion of this literature study emphasizes the importance of recognizing the impact of academic stress on students' conflict resolution abilities at school. Holistic and sustained efforts are needed to reduce academic stress and strengthen students' social skills, including the development of communication skills, empathy, emotional management, and critical and creative thinking. This can create an inclusive, supportive, and safe learning environment at school, where students can grow and develop optimally.